Deposition and transport of linezolid mediated by a synthetic surfactant Synsurf® within a pressurized metered dose inhaler: a Calu-3 model - van Rensburg L; van Zyl JM; Smith J (Dove Medical Press, 2018)
Lyné van Rensburg,1 Johann M van Zyl,1 Johan Smith2 1Division of Clinical Pharmacology, Department of Medicine, Faculty of Medicine and Health Sciences, Stellenbosch University, Tygerberg, South Africa; 2Department of Pediatrics, Tygerberg Children’s Hospital, Faculty of Medicine and Health Sciences, Stellenbosch University, Tygerberg, South Africa Background: Previous studies in our laboratory demonstrated that a synthetic peptide containing lung surfactant enhances the permeability of chemical compounds through bronchial epithelium. The purpose of this study was to test two formulations of Synsurf® combined with linezolid as respirable compounds using a pressurized metered dose inhaler (pMDI). Methods: Aerosolization efficiency of the surfactant-drug microparticles onto Calu-3 monolayers as an air interface culture was analyzed using a Next Generation Impactor™. Results: The delivered particles and drug dose showed a high dependency from the preparation that was aerosolized. Scanning electron microscopy imaging allowed for visualization of the deposited particles, establishing them as liposomal-type structures (diameter 500 nm to 2 µm) with filamentous features. Conclusion: The different surfactant drug combinations allow for an evaluation of the significance of the experimental model system, as well as assessment of the formulations providing a possible noninvasive, site-specific, delivery model via pMDI. Keywords: Calu-3, pMDI, linezolid, delivery vehicle, pulmonary surfactant, aerosolized particles